Technicity as a structural mediation in the process of transit of audiences: notes for contemporary organizational communication - Pieniz, Mônica (Organicom, 2015)
This article provides notes for organizational communication using the reflection on elements of a doctoral thesis thataimed at understanding the process of audiences, where receivers become broadcasters when sharing their perceptionsof soap operas on the Twitter. The results showed contents and motivations related not only to the plot, but other aspectsof the public’s relationship with the organization, showing the need for organizations to become cross-media receivers andbroadcasters in relation to different audiences.